2017
DOI: 10.1177/2158244017691563
|View full text |Cite
|
Sign up to set email alerts
|

Negotiation and Management Strategies of Street Vendors in Developing Countries

Abstract: The existing literature on the relationship between regulators and street vendors remain fragmented and limited to specific countries and contexts. This article presents a narrative review of the existing literature on the relationship between regulators and street vendors, and through that creates a unified picture of an otherwise fragmented literature and knowledge base. The concepts of negotiation, power, social network, and perception are used to analyze the various strategies street vendors have used in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 22 publications
2
33
0
4
Order By: Relevance
“…However, staff identified that there is now a lack of adequate consultation since this disconnect took root and they will need to work better and more meaningfully with trading organisations moving forward. This type of collaboration with trading associations is also encouraged in the literature (Forkuor, Akuoko, and Yeboah 2017;Goodfellow 2016;Roever and Skinner 2016;Brown, Lyons, and Dankoco 2010). In Durban specifically, it will entail a necessary return to previous practices and to addressing current policy concerns (Goodfellow 2016;Roever and Skinner 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, staff identified that there is now a lack of adequate consultation since this disconnect took root and they will need to work better and more meaningfully with trading organisations moving forward. This type of collaboration with trading associations is also encouraged in the literature (Forkuor, Akuoko, and Yeboah 2017;Goodfellow 2016;Roever and Skinner 2016;Brown, Lyons, and Dankoco 2010). In Durban specifically, it will entail a necessary return to previous practices and to addressing current policy concerns (Goodfellow 2016;Roever and Skinner 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Since the early 1990s, when the Warwick Junction Pilot Project first started and involved traders in the development of and investment in organized markets, Durban has been recognised for its success with informal trading (Skinner 2008;Skinner and Valodia 2003;Lund and Skinner 2004). Often, literature about informal trade in other cities states that traders lack organization and collective voice to negotiate with the local government for space in the public realm (Forkuor, Akuoko, and Yeboah 2017;Goodfellow 2016;Roever and Skinner 2016;Brown, Lyons, and Dankoco 2010). These studies reference Durban as the best example of involving trading associations in local governance and management processes of the markets (Goodfellow 2016;Roever and Skinner 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They actively participate in a subtle struggle to negotiate and contest the constraints faced in their daily operations. Indeed, such negotiation strategies are carried out at the macro level – between the organised group and local authorities, and also at the micro level – between the vendors and regulators (Forkuor et al, : 8). In this research I argue that street vendors’ ability to build networks in the form of ‘social infrastructure’ with various stakeholders, such as customers, informal organisers, and suppliers, in addition to their use of new technology, allows them to negotiate and amplify their existence in everyday urban life.…”
Section: The Next Generation Of Traders: Middle Class Street Vendors mentioning
confidence: 99%
“…Municipalities often perceive and portray street vendors as negatively affecting the attractiveness and beauty of their cities, as a source of congestion and poor environmental sanitation; their structures are seen as damaging the "aesthetic qualities of urban settlements. Street vendors are often described as bullies and illegitimate, hindering the ability of cities to modernize and achieve global status (Forkuor et al, 2017). Because of this perception, local governments in various cities in Indonesia try to control and relocate street vendors.…”
Section: Introductionmentioning
confidence: 99%